Meat quality of suckling goat raised in differents feeding systems - Norivaldo Lima Santos; Wandrick Hauss de Sousa; Maria das Graças Cunha Gomes; Ana Sancha Malveira Batista; João Paulo de Farias Ramos; Felipe Queiroga Cartaxo; Aianne Batista Lira; Iara Tamires Rodrigues Cavalcante (Acta Scientiarum. Animal Sciences, 2020)
The objective of this work was to evaluate the effect of three breeding systems on the organoleptic quality and the physico-chemical composition of kids goat meat. Were used thirty newborn baby goats of 3.35 kg ± 0.65 kg crossed Parda Alpina x Undefined Race (SPRD) submitted to three breeding systems: Traditional system-TS; Intensive Feeding System without Concentrate- IS and Intensive Feeding System with Concentrate- IS+C. When the goats reached 12 kg, the animals were slaughtered and chemical and physical analyzes were performed in the evaluation of the meat and sensorial. The experimental design was completely randomized, submitted to analysis of variance and compared by the Tukey test and Ryan-Einot-Gabriel-Welsh at 5%. All analyzed variables were also submitted to Pearson correlation. The meat of the goats submitted to IS+C and IS presented higher intramuscular fat content and better flavor and aroma scores. A of Goats that used concentrated ration (TS and IS+C) showed a more intense red color in the meat than the animals that did not receive concentrate in their diets, besides presenting higher lipid contents in their composition, better scores for these two organoleptic characteristics. The chemical composition of goat meat in both breeding systems indicates that it is low in fat and high in moisture and therefore classified as very tender and juicy. The meat obtained from the IS+C, in general, presented better attributes than the others, believing it in the markets of meat of high quality.